Prevalence of obesity and related factors in schoolchildren aged 3 to 4 years - Gemma Serral; Catalina Londoño-Cañola; Xavier Continente; Silvia Brugueras; Francesca Sanchez-Martínez; Carlos Ariza (Elsevier, 2024)
Objective: To describe the prevalence of obesity and analyse possible differences in it according to sociodemographic characteristics, diet, physical activity, screen use and family perception of the weight and dietary habits of schoolchildren aged 3 to 4 years in Barcelona. Methods: We conducted a cross-sectional study in a representative sample of schools selected based on the socioeconomic status (SES) of the corresponding neighbourhood and school ownership. We selected 101 schools in Barcelona and recruited pupils aged 3 to 4 years during the 2016-17 academic year (n = 2936 children). Anthropometric measurements were taken in each participant. Family members completed a questionnaire on eating habits, physical activity, sleeping hours, screen use and the family's perception of the child's weight and diet. The primary variable was the body mass index (BMI) for age and sex, subsequently categorised as normal weight, overweight or obese. Results: Approximately 7.0% of girls and 7.1% of boys aged 3 to 4 years presented obesity. The prevalence of obesity (8.3%) was higher in neighbourhoods of lower SES compared to those of higher SES (5.2%; p = .004). Parents of children with obesity reported that the child had some excess weight or excess weight in 46.9% of cases, 3.9% indicated the child's weight was appropriate and 0.9% that the child was a little underweight or underweight (p < .001). Discussion: The prevalence of obesity in children aged 3 to 4 years is high. There are social and geographical inequalities, and obesity was more prevalent in areas of lower SES. A large percentage of the families of children with obesity do not consider that the child's weight is excessive. Resumen: Objetivo: Describir la prevalencia de obesidad y analizar posibles diferencias según características sociodemográficas, alimentación, actividad física, visionado de pantallas y percepción familiar sobre el peso y alimentación de sus hijos/as en escolares de 3 a 4 años de Barcelona. Método: Estudio transversal a una muestra representativa de escuelas según nivel socioeconómico (NSE) del barrio y titularidad. Se seleccionaron 101 escuelas de Barcelona y se reclutó al alumnado de 3 a 4 años en el curso 2016-17 (N = 2.936 niños/as). Se tomaron medidas antropométricas. Los familiares respondieron a un cuestionario de hábitos sobre alimentación, actividad física, horas de sueño, visionado de pantallas y percepción familiar sobre el peso y la alimentación de su hijo/a. La variable principal fue el Índice de Masa Corporal (IMC), calculado por edad y sexo, y categorizado en: normopeso, sobrepeso u obesidad. Resultados: El 7,0% de las niñas y el 7,1% de los niños de 3-4 años presentaron obesidad. En los distritos de NSE desfavorecido hubo mayor obesidad (8,3%) que en los más favorecidos (5,2%; p = 0,004). Los padres/madres de niños/as cuyo peso fue de obesidad declararon que el peso de su hijo/a era un poco excesivo o excesivo en un 46,9%, en un 3,9% indicaron que era adecuado y el 0,9% que era un poco bajo o bajo (p < 0,001). Discusión: La prevalencia de obesidad en niños y niñas de 3 a 4 años es elevada. Existen desigualdades sociales siendo superior en áreas de NSE más desfavorecidas. Un elevado porcentaje de familias de niños/as con obesidad no consideran que el peso de sus hijos/as sea excesivo.